For love of people, culture and society: expert commentary - McLean, Monica; LeFanu, Sarah; Bruce, Susan (Sense Publishers, 2016)
The commentary is on a set of poems about the teaching of social sciences and sensitive topics. It takes the poems as pedagogical case studies, pointing out what can be learning from them.